2021
DOI: 10.1088/1742-6596/1878/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of Lean Manufacturing Implemented Practices in SME in Sabah State: TQM And TPM Practices Approach

Abstract: This study aims to evaluate the awareness of implemented practices that already applied and the implementation of lean manufacturing practice of Total Quality Management (TQM) and Total Productive Maintenance (TPM) on Small Medium Enterprise (SME) companies in Sabah. Regarding the implementation of TQM and TPM practices of lean manufacturing, this study evaluates the awareness implementation of lean manufacturing practices TQM and TPM among manufacturing company located in Sabah before analyzing the respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Independent organizations began developing standards in the last decades of the 20th century to support the rise of Quality Management Systems (QMS); at the time, the concept of Total Quality Management (TQM) originated as an American response to Japan's quality revolution [124]. In the literature, TQM is often discussed with or without TPM or JIT in a framework of lean manufacturing or continuous improvement to achieve world-class manufacturing [23,35,37,41,[51][52][53][54][55][58][59][60][61][62][63][64][66][67][68][69][70]72,74,77,78,81,125], and the literature is inaccurate in encapsulating TQM and its country of origin (i.e., US or Japan) [115,126]. TQM is a company culture in which all employees actively participate in quality improvement [127].…”
Section: After the Appearance Of Tpm And The Advent Of Stpmmentioning
confidence: 99%
“…Independent organizations began developing standards in the last decades of the 20th century to support the rise of Quality Management Systems (QMS); at the time, the concept of Total Quality Management (TQM) originated as an American response to Japan's quality revolution [124]. In the literature, TQM is often discussed with or without TPM or JIT in a framework of lean manufacturing or continuous improvement to achieve world-class manufacturing [23,35,37,41,[51][52][53][54][55][58][59][60][61][62][63][64][66][67][68][69][70]72,74,77,78,81,125], and the literature is inaccurate in encapsulating TQM and its country of origin (i.e., US or Japan) [115,126]. TQM is a company culture in which all employees actively participate in quality improvement [127].…”
Section: After the Appearance Of Tpm And The Advent Of Stpmmentioning
confidence: 99%
“…This situation highlights that SMEs with a shorter operational history lack fundamental knowledge about lean methodologies, and the prevailing concept in the survey is that of a toolkit for improving production. Furthermore, another study conducted on 31 SMEs in Sabah, Malaysia, revealed that approximately 74% of surveyed SMEs lack any type of knowledge or experience in lean methodologies, resulting in a significant lack of awareness about what Lean Manufacturing truly entails (Adzrie et al 2021). The absence of commitment at different organizational levels of SMEs was also identified as an additional barrier.…”
Section: Introductionmentioning
confidence: 99%
“…TQM: As Adzrie et al [13] point out, this is a management system based on the principle that each member of staff must be committed to maintaining a high standard of work in all aspects of the business activity.…”
Section: Introductionmentioning
confidence: 99%